Faktor yang Berhubungan dengan Kelelahan Kerja pada Perawat di Ruang IGD dan ICU BLUD RS Benyamin Guluh Kab. Kolaka Tahun 2023 - Nurjannah, Widiyanti; Muchtar, Febriana; Prianti, Indah Ade (Bagian Penelitian & Pengabdian Masyarakat STIKES Adi Husada, 2023)
Background: Work fatigue is a condition experienced by workers as a result of job responsibilities that have an impact on endurance and efficiency at work. Fatigue is part of occupational health and safety issues because it can cause accidents at work. Nurses are one of the workforce in hospitals with the responsibility of providing optimal service to patients. The demands of the work carried out by nurses can cause fatigue. Aims: The purpose of this study was to determine what factors are associated with work fatigue in nurses in the emergency room and ICU BLUD RS Benyamin Guluh Kolaka Regency in 2023. Methods: This study was conducted in the field of emergency room services and the field of ICU care BLUD Benyamin Guluh Hospital Kolaka Regency in June 2023. The population and sample of this study were all nurses who worked in the emergency room and ICU BLUD RS Benyamiin Guluh Kolaka Regency which amounted to 47 nurses. Results: The results showed that workload (p = 0.032, r = 314), attitude (P = 0.025, r = 0.326), and tenure (p = 0.018, r = 0.343) are factors that are positively related or proportional to job fatigue, while work shifts (p = 0.531, r = 0.094) are not related to job fatigue. Conclusion: Workload, attitude, and tenure are positively related or directly proportional to job fatigue in nurses in the emergency room and ICU BLUD Benyamin Guluh Hospital Kolaka Regency. Based on the results of the study, it is necessary to increase teamwork in completing work, the hospital can add training to nurses so that they are not monotonous in their work, create a mutually supportive work atmosphere, and nurses with a work period of <5 years need to pay attention to their working conditions and environment so that they can adapt and be able to organize work.